Changes in aldehyde oxidase activity and gene expression in Solarium lycopersicum L. shoots under salicylic acid pretreatment and subsequent salt stress - Horváth, Edit (Acta Biologica Szegediensis, 2011)
The plant hormone abscisic acid (ABA) plays essential role in adaptation and response processes in plants by modifying a number of gene expressions. Aldehyde oxidases (AOs) may participate in stress responses, because it catalyzes the oxidation of abscisic aldehyde to ABA, in the last step of ABA synthesis. In this work the expression levels of the three known tomato AO genes were monitored by quantitative real-time PCR (QRT-PCR) after 3-weeks pretreatment with two salicylic acid (SA) concentrations followed by 1-week-long salt stress. The 10-4 M SA pre-treatment, but not the 10-7 M SA, increased the SlAO2 gene expression, and both SA concentrations increased the transcript amount of SlAO3. The high salinity treatment for one week increased slightly only SlAO2 gene expression in the control shoots. The AO1 enzyme activity, which was studied with native polyacrylamide gel electrophoresis, was on control level after 4-week pre-treatment with 10-4 M SA, but decreased using 10-7 M SA. One-week 100 mM NaCl treatment decreased the activity of the AO1 isoenzyme excluding the 10-7 M SA pre-treatment. These moderate changes in the gene expressions and enzyme activities may contribute in the acclimation of 10-4 M SA pre-treated tomato plants to subsequent salt stress.